1976
DOI: 10.1017/s0016756800047609
|View full text |Cite
|
Sign up to set email alerts
|

Some conventional potassium–argon and 40Ar/39Ar age studies of glauconite

Abstract: 40 Ar/ 39 Ar age studies of some glauconites from well-known stratigraphical horizons reveal unexpectedly high ages compared with the conventional K-Ar age determinations. These have been interpreted in terms of nuclear and physico-chemical reactions sustained by the glauconites in the reactor. These impose severe limitations on the use of glauconite in the 40 Ar/ 39 Ar irradiation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Glauconitic minerals are commonly used for K-Ar dating, but several studies (Brereton et al, 1976;Foland et al, 1984;Kapusta et al, 1997) have reported problems obtaining reliable ages for glauconite with the 40 Ar/ 39 Ar variation of the method. These problems are attributed to recoil of 39 Ar during irradiation, which leads to underestimates of the K content of the samples, thereby resulting in the calculation of anomalously old ages.…”
Section: Ar/ 39 Ar Analysis Of Glauconitic Mineralsmentioning
confidence: 99%
“…Glauconitic minerals are commonly used for K-Ar dating, but several studies (Brereton et al, 1976;Foland et al, 1984;Kapusta et al, 1997) have reported problems obtaining reliable ages for glauconite with the 40 Ar/ 39 Ar variation of the method. These problems are attributed to recoil of 39 Ar during irradiation, which leads to underestimates of the K content of the samples, thereby resulting in the calculation of anomalously old ages.…”
Section: Ar/ 39 Ar Analysis Of Glauconitic Mineralsmentioning
confidence: 99%
“…The neutrons transfer kinetic energy to 39 Ar atoms that causes their displacement in the mineral structure (Turner and Cadogan, 1974), with the magnitude of recoil energy (hence displacement) increasing with incident neutron energy. These so-called recoil effects can have important consequences for 40 Ar/ 39 Ar geochronology and may create problems with interpreting the age spectra of altered minerals (e.g., Hess and Lippolt, 1986;Lo and Onstott, 1988;Min et al, 2001;Nomade et al, 2004) and fine-grained materials such as meteorites, aphyric lavas, glauconite and phyllosilicates (Turner and Cadogan, 1974;Brereton et al, 1976;Huneke and Smith, 1976; Halliday, 1978;Foland et al, 1992Foland et al, , 1993Dong et al, 1997). Recoil effects may also complicate grain size studies (Markley et al, 2002) and multi-diffusion domain (MDD) theory .…”
Section: Introductionmentioning
confidence: 99%
“…Kunk and Brusewitz (1987) documented the problem of the 39 Ar recoil effect on an illite/smectite mixed-layer mineral placed in a quartz vial before irradiation. They could determine the amount of recoil, which has also been mentioned by Yanase et al (1975), Brereton et al (1976) andFoland et al (1984) on glauconite-type minerals. However, loss of 39 Ar, which has been related to structural alterations attendant on irradiation, may not be the rule for all clay minerals, since Hunziker et al (1986) and Reuter and Dallmeyer (1987a,b), for instance, reported cases of similar conventional K-Ar and 40 Ar/ 39 Ar ages for different size fractions of illite-type minerals.…”
Section: Sm-nd Datingmentioning
confidence: 61%